Quantitative Easing and Wealth Inequality: The Asset Price Channel. (8th February 2023) - De Luigi, Clara; Feldkircher, Martin; Poyntner, Philipp; Schuberth, Helene
Abstract: We assess the impact of the ECB's unconventional monetary policy, specifically of quantitative easing (QE), on the distribution of household wealth in nine euro area countries. For this purpose, we estimate the effects of a QE shock on housing and risky financial asset prices by means of local projections. We then use these estimates to carry out micro‐simulations based on data from the Household Finance and Consumption Survey (HFCS). For the majority of the countries under review, expansionary QE via asset prices leads to net wealth inequality increases when measured using wealth indicators that are sensitive to changes at the tails of the wealth distribution. This finding contrasts with results based on the Gini coefficient which point to an equalizing impact of QE. One‐third of the households in our sample holds neither housing nor financial wealth and is thus not directly affected by QE measures through the asset prices channel.